1991
DOI: 10.3109/00365529108998626
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation to Short-Chain Fatty Acids and Lactate in Human Faecal Batch Cultures Intra- and Inter-Individual Variations versus Variations Caused by Changes in Fermented Saccharides

Abstract: The fermentation to short-chain fatty acids, lactate, and ammonia from several non-starch polysaccharides, glucose, and albumin was investigated in 16.6% faecal homogenates. Increasing concentrations (0-30 mg/ml) of glucose, wheat bran, pectin, ispaghula, cellulose, or albumin incubated for 24 h in homogenates pooled from three individuals increased short-chain fatty acid production linearly. Amounts and ratios of short-chain fatty acids formed were highly dependent on the type of substrate fermented. Fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…In addition it could be confirmed by microbial studies of the incubation fluid that the numbers of total viable counts, lactobacilli, enterobacteria, streptococci and clostridia were in same range as respective numbers present in the cecal fluid of the donor animals [22]. In comparison with fecal batch cultures as described by Mortenson et al [23], it is a further advantage of COSITEC that the accumulation of end-products cannot occur due to its semicontinuous character and that the microbial population is obtained from those parts of the hindgut which are physiologically relevant. It also has to be taken into account that the composition and the ratio between living and autoclaved microbes of the fecal flora are different from the respective cecal and colonic flora.…”
Section: Discussionmentioning
confidence: 76%
“…In addition it could be confirmed by microbial studies of the incubation fluid that the numbers of total viable counts, lactobacilli, enterobacteria, streptococci and clostridia were in same range as respective numbers present in the cecal fluid of the donor animals [22]. In comparison with fecal batch cultures as described by Mortenson et al [23], it is a further advantage of COSITEC that the accumulation of end-products cannot occur due to its semicontinuous character and that the microbial population is obtained from those parts of the hindgut which are physiologically relevant. It also has to be taken into account that the composition and the ratio between living and autoclaved microbes of the fecal flora are different from the respective cecal and colonic flora.…”
Section: Discussionmentioning
confidence: 76%
“…SCFA production: Several investigations have shown that higher proportions of propionate and butyrate are produced by fermentation in vitro and in vivo from gum arabic than from other hydrocolloids such as pectin (May et al, 1994;Michel et al, 1998;Mortensen, Hove, Clausen, & Holtug, 1991;Titgemeyer, Bourquin, Fahey, & Garleb, 1991;Topping, Mock, Trimble, Storer, & Illman, 1988). Table 2 shows a comparison of several investigations, giving also the source of the bacteria used.…”
Section: Physiological Action: Gum Arabic a Dietary Fibre And Prebioticmentioning
confidence: 99%
“…Certain oligosaccharides such as fructooligosaccharides and galactooligosaccharides and the polysaccharide inulin, may be fermented preferentially by bifidobacteria, which has given rise to the concept of prebiotics, nondigestible food components that selectively stimulate one or a limited number of beneficial bacteria within the gut [15,21]. Non-starch polysaccharides include pectin, arabinogalactan, inulin, guar gum and hemicellulose, which are readily fermented by the colonic microbiota, and lignin and cellulose, which are much less fermentable [22,23]. Endogenous carbohydrates, chiefly from mucin and condroitin sulfate, contribute about 2 -3 g/day of fermentable sub-strate [8].…”
Section: Carbohydratementioning
confidence: 99%